A comparative study of packet combining based error recovery schemes for wireless networks. (26th August 2014) - Wang, Sheng–Shih; Lee, Pei–Chun; Lin, Kan–Yen; Yeh, Tzu–Chang
To provide reliable communications in wireless environments, two fundamental error control mechanisms, automatic repeat request (ARQ) and forward error correction (FEC) are proposed. However, the ARQ mechanism may suffer frequent retransmissions and the FEC mechanism incurs bandwidth overhead. To reduce the number of retransmissions and support efficient correction, previous studies have proposed numerous packet combining based error recovery schemes. This study investigates the recovery performance of three packet combining based error recovery schemes, including the extended ARQ (EARQ), the merge strategy in the simple packet combining (SPaC–M), and the destination packet (DPC) schemes through the mathematical analysis and simulations. Results present that the EARQ outperforms the SPaC–M and the DPC in recovery speed in case of a large packet length and a high bit error rate. However, the EARQ is not suggested if the space overhead is the major consideration.